Modelling and experimental study of pressure elution of high‐viscosity substances with a low‐viscosity liquid from granular bed. (6th June 2016) - Błaszczyk, Mariola M.; Sęk, Jerzy P.; Przybysz, Łukasz
Abstract: The pressurized elution of oily substances with high viscosities from porous granular media is of primary importance from the point of view of enhanced oil recovery techniques and technologies. Accurate prediction of such processes can lead to their technical and financial optimization. Modelling considerations existing in the literature neglect many factors affecting elution phenomena. Additionally, extensive experimental data are not available. Other description methods are needed to enable more precise descriptions of the process. This paper develops a theoretical model which considers the dependence of oily substance elution on many parameters characterizing porous granular beds and flowing liquids. The influence of grain size distribution in the bed was considered, as well as the finite dimensions of the real bed. The bed saturation at the beginning of the process was also included in the modelling work together with eluent flow rate and media viscosity. Theoretical considerations were verified and supported with extensive experimental measurements.